Evaluasi Potensi Interaksi Obat pada Pengobatan Pasien ISPA Anak Rawat Inap di Rumah Sakit Kota Banjarmasin. - Aris Fadillah; Hasniah Hasniah; Juwita Ramadhani; Muliyani Muliyani; Muhammad Hasan Andriyanto; Nily Su’aida (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Drug interactions represent a clinically significant drug-related problem that may compromise therapeutic efficacy and increase the risk of adverse events. In pediatric patients with acute respiratory infections (ARIs), the use of multiple medications is common, potentially elevating the likelihood of drug interactions. Objective: This study aimed to evaluate the potential drug–drug interactions in hospitalized pediatric patients diagnosed with ARIs in Banjarmasin, Indonesia. Methods: A retrospective descriptive study was conducted using secondary data retrieved from the Hospital Management Information System. All medication regimens administered to pediatric inpatients with ARIs from January to June 2024 were analyzed. Drug interaction screening was performed using the Drugs.com Interaction Checker application. Results: Among 81 patients who met the inclusion criteria, 7 patients (8.64%) received treatment regimens with potential drug–drug interactions, accounting for a total of 8 interaction events (mean 1.14 interactions per affected patient). All identified interactions were classified as moderate in severity. Pharmacodynamic interactions were predominant (87.50%), whereas pharmacokinetic mechanisms comprised the remaining 12.50%. The most frequently observed potential interaction was between gentamicin and ceftriaxone (62.50%). Conclusion: Although the prevalence of potential drug interactions in this study was relatively low, their presence—particularly moderate-level pharmacodynamic interactions—warrants systematic clinical pharmacy monitoring to enhance patient safety and prevent undesirable clinical outcomes in pediatric ARI management.